2018
DOI: 10.1002/fsn3.835
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan‐based coatings enriched with savory and/or tarragon essential oils on postharvest maintenance of kumquat (Fortunella sp.) fruit

Abstract: The present study assessed the ability of chitosan‐based coatings incorporating savory and/or tarragon essential oils (EOs) to preserve the postharvest quality of kumquats. Changes in weight loss, titratable acidity, total soluble solids, and vitamin C content were determined over 30 days of storage at 7°C. Savory (Satureja hortensias L.) essential oil was characterized by thymol (29.1%), carvacrol (26.6%), and γ‐terpinene (24.72%) as major constituents. While, in the tarragon (Artemisia dracunculus L.) essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 32 publications
3
17
0
Order By: Relevance
“…Also the improvement of the memory, learning, as well as the motor coordination by polyphenols may be originated from their ability to attenuate the oxidative stress and inflammation (via modification of NF-κB levels and cytokines). Additionally, kumquat according to Hosseini et al (38) is a good source of vitamin C to which the protective effect of kumquat fruits against brain aging may be attributed. Monacelli et al (39) declared that oxidative stress, over production of the inflammatory agents, telomere attrition, as well as chromatin disorganization can be suppressed by vitamin C. Also, the two hallmarks of biological aging (immune-senescence and inflammaging) can be modulated by vitamin C. Mani and Parle (40) concluded that the elevation in acetyl cholinesterase activity and the memory deficits can be reversed by the oral administration of carrot seeds extract.…”
Section: Discussionmentioning
confidence: 99%
“…Also the improvement of the memory, learning, as well as the motor coordination by polyphenols may be originated from their ability to attenuate the oxidative stress and inflammation (via modification of NF-κB levels and cytokines). Additionally, kumquat according to Hosseini et al (38) is a good source of vitamin C to which the protective effect of kumquat fruits against brain aging may be attributed. Monacelli et al (39) declared that oxidative stress, over production of the inflammatory agents, telomere attrition, as well as chromatin disorganization can be suppressed by vitamin C. Also, the two hallmarks of biological aging (immune-senescence and inflammaging) can be modulated by vitamin C. Mani and Parle (40) concluded that the elevation in acetyl cholinesterase activity and the memory deficits can be reversed by the oral administration of carrot seeds extract.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the application of CS coating enriched with lactoperoxidase, aloe vera gel, savory and/or tarragon essential oils, phenolic compounds, and organic acid on mango, litchi, fig, cherimoya, kumquat, and apple fruits reduced the losses of AA during storage, respectively [ 40 , 75 , 76 , 77 , 78 , 79 , 80 ]. Benitez et al [ 81 ] also demonstrated that the effectiveness of the CS coatings in kiwifruit slices on oxidative degradation of AA depends on the organic acid used in the formulation of coating.…”
Section: Reactive Oxygen Species and Antioxidant Systemsmentioning
confidence: 99%
“…The Xunwu mandarin is a special citrus variety of Xunwu County of Ganzhou City in Jiangxi Province, which is also a famous cultivation area. The kumquat is produced by small fruit trees in the Rutaceae family, which have been widely cultivated in many countries in recent years [ 5 , 6 ]. It is excellent source of nutrients and phytochemicals, including ascorbic acid, carotenoids, flavonoids and essential oils (EOs), which are often used in traditional medicine [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%